Preparation and Evaluation of In Vitro Release Kinetics of Theophylline Loaded Matrix Tablet Based on Eudragit NE 30 D and Eudragit RS 30 D - Uddin, Mohammad Borhan; Chowdhury, Jakir Ahmed; Azam, Kazi Rashidul; Jalil, Reza-ul; Reza, Md Selim (Dhaka University Journal of Pharmaceutical Sciences, 2010)
In the present study efficiency of Eudragit NE 30 D and RS 30 D as matrix forming materials was investigated. It was found that theophylline loaded granules prepared with these two polymers could not sustain drug release for a significant period of time. However, compression of these granules into tablets retarded drug release for up to 7 hours. Release was similar with both of the polymers. Effects of fillers and rate modifiers on drug release have been assessed. Incorporation of lactose and starch caused substantial release of theophylline from both the polymeric systems. Avicel PH 101 intensified the retardation effect of both NE 30 D and RS 30 D on theophylline release. Hydrophobic excipients also show retardation of release from both NE 30 D and RS 30 D. Key words: Eudragit RS 30 D; Eudragit NE 30 D; Theophylline; Matrix system; Controlled release DOI: 10.3329/dujps.v8i2.6030 Dhaka Univ. J. Pharm. Sci. 8(2): 153-159, 2009 (December)